2012
DOI: 10.1590/s0004-27492012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for Graves' ophthalmopathy: a systematic review and meta-analysis of randomized controlled trials

Abstract: Purpose: To evaluate the efficacy of radiotherapy (RT) with total dose of 20 Gy (RT 20 Gy) in the treatment of Graves' ophthalmopathy. Methods: A systematic review and metaanalysis of randomized controlled trials was performed comparing RT 20 Gy with or without glucocorticoid to cli nical treatments for Graves' ophthalmopathy. The MEDLINE, EMBASE, Cochrane Library databases and recent relevant journals were searched. Relevant reports were reviewed by two reviewers. Response to radiotherapy was defined as clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
0
24
0
6
Order By: Relevance
“…This treatment had already been proposed in 1983 by Bartalena et al [27], who reported a better outcome of the combined therapy. Several studies confirmed the efficacy of orbital irradiation as based on the meta-analysis by Viani et al [28], although Otsuka et al [29] found no significant differences in terms of the therapeutic effect between groups treated with steroid pulses with or without orbital irradiation. There are no large RCTs comparing the advantage of this combined treatment over IV glucocorticosteroids alone [28,30,31].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This treatment had already been proposed in 1983 by Bartalena et al [27], who reported a better outcome of the combined therapy. Several studies confirmed the efficacy of orbital irradiation as based on the meta-analysis by Viani et al [28], although Otsuka et al [29] found no significant differences in terms of the therapeutic effect between groups treated with steroid pulses with or without orbital irradiation. There are no large RCTs comparing the advantage of this combined treatment over IV glucocorticosteroids alone [28,30,31].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies confirmed the efficacy of orbital irradiation as based on the meta-analysis by Viani et al [28], although Otsuka et al [29] found no significant differences in terms of the therapeutic effect between groups treated with steroid pulses with or without orbital irradiation. There are no large RCTs comparing the advantage of this combined treatment over IV glucocorticosteroids alone [28,30,31]. As reported in a randomised study, lower orbital doses of 12 Gy were sufficient in reducing soft tissue changes, and higher doses were required in patients with ocular motility impairment [32].…”
Section: Discussionmentioning
confidence: 92%
“…According to medical literature the dose of 20 Gy can be considered the optimal dose for orbital RT of TAO. The cumulative dose is usually fractionated in 10 daily doses over a 2-week period to reduce the cataractogenic effect [221]. Higher cumulative doses of RT does not improve the effectiveness of treatment [222].…”
Section: Radiotherapymentioning
confidence: 99%
“…Radiation retinopathy is an extremely rare complication of RT. Systemic microvascular disease due to diabetes mellitus (DM) or to previous chemotherapy may increase the risk for radiation retinopathy [221].…”
Section: Radiotherapymentioning
confidence: 99%
“…A systematic review of the risks and benefits of radiotherapy, with or without the use of glucocorticoids, for the treatment of Graves' ophthalmopathy presented in this issue is the most comprehensive ever published in the world literature (2) . The authors identified 359 scientific articles on the subject in the various data sources and selected the eight ones that were randomized controlled trials, with data available.…”
Section: Wallace Chamonmentioning
confidence: 99%